Effect of Cultivar and Planting Date on Soybean Response to Dicamba - Wesley France; Jason Norsworthy; Trent Roberts; Jeremy Ross; Tom Barber; Edward Gbur (International Journal of Agronomy)
Off-target movement of dicamba has been blamed for damaging millions of hectares of soybean in the United States since registration of the herbicide for use in dicamba-resistant cotton and soybean. Understanding the effect of a low dose of dicamba on non-dicamba-resistant soybean across multiple cultivars, growth stages, and planting dates could help producers better understand the implication of current management practices on yield loss from dicamba in fields where non-dicamba-resistant soybean are grown. A field experiment was conducted in 2019 in Fayetteville and Stuttgart, Arkansas, to evaluate the impact of planting date on response of soybean to a low dose of dicamba. The hypothesis of the planting date experiment was that soybean injury and yield loss will differ depending on planting date and dicamba application timing. Additionally, an experiment was conducted in 2018 and 2019 in Fayetteville to assess whether cultivars differ in sensitivity to dicamba. The hypothesis of the cultivar experiment was that genetic differences of soybean cultivars will allow for differential tolerance to dicamba. In the cultivar experiment, “Eagle DrewSoy” was identified as having enhanced tolerance to dicamba based on reduced injury (47% at R1 and 26% at V3) over both experimental years and locations. Soybean height in this experiment was affected only by application timing. In the planting date experiment, planting after mid-June resulted in reduced yields from dicamba injury. Dicamba exposure reduced yield at the July planting date (61% reduction from nontreated) more severely when compared to dicamba-treated plots of other planting dates (94% average relative yield among other planting dates), indicating that the negative effects of dicamba are increasingly deleterious for soybean planted later in the growing season. Maximum injury manifestation was generally delayed at later planting dates, indicating that dicamba may have been metabolized more slowly.